Kedudukan dan peran perempuan aceh di depan hukum - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstract Conflict situation will influence to its people. In the hostile situation, women and children are the most fragile groups as victims. Aceh history has proven to us that women had a central position. Queen Taj al Alam Tsafiattuddin and Princess Pahang were two women public figure on law, democracy and governance. Meanwhile, Cut Nyak Dhien, Cut Nyak Karti are hero when they struggled for independence. The most hostile situation for women and children in Aceh was in Military Operation Target. Women rights and their pride have been harassed. Moreover, when qanun is promulgated, women only have strict liberty to assess their rights. This situation is very relevant when tsunami hit this province and hit them. Key words: qanun, hostile situation